Godność, codzienność, wsparcie osób starszych z niepełnosprawnością - SZCZUPAŁ, BERNADETA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Bernadeta Szczupał, Dignity, everyday life, support for seniors with disabilities, Interdisciplinary Contexts of Special Pedagogy, No. 22, Poznań 2018. Pp. 15–26. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.02 The process of ageing is an inevitable life phenomenon in both the individual and social aspects. With the growing life expectancy of humans, the way of living in the old age becomes a challenge in the context of respect for the dignity of the elderly. In this article, I present selected theoretical issues concerning the sense of dignity, everyday life and helplessness of elderly people with disabilities, which is unfortunately often associated with it. I also show the complexity of contemporary problems and expectations and the challenges faced by older people with disabilities.